Can informed consent to research be adapted to risk?. Issue 7 (28th October 2014) - Bromwich, Danielle; Rid, Annette
Abstract : The current ethical and regulatory framework for research is often charged with burdening investigators and impeding socially valuable research. To address these concerns, a growing number of research ethicists argue that informed consent should be adapted to the risks of research participation. This would require less rigorous consent standards in low-risk research than in high-risk research. However, the current discussion is restricted to cases of research in which the risks of research participation are outweighed by the potential clinical benefits for the individual research participant. Furthermore, current proposals do not address the concern that risk-adapted informed consent may result in enrolling participants into research without their autonomous authorisation. In this paper, we show how the standard view of informed consent—consent as autonomous authorisation—can be adapted to risk even when the research does not have a favourable risk-benefit profile for the participant. Our argument has two important implications: first, it implies that current and proposed consent standards are not adequately calibrated to risk and, second, that consent standards also need to be adapted to factors other than risk.